Well, isn't that just a happy little equation we have here! When you multiply 4k by k, you simply multiply the coefficients (4 and 1) to get 4, and then add the exponents of k, which gives you k^2. So, 4k x k equals 4k^2. Just remember, there are no mistakes in math, only happy accidents!
2
Remember in basic Algebra we learned that all variables can be substituted as 1's If needed. So lets do that: -k - 4k = -1 - 4(1) = -5 So now we can rewrite this removing the 1's we put in: -k - 4k = -5k
k=-2
Tangent line equation: y = x+k Circle equation: x^2 +y^2 = 25 If: y = x+k then y^2 = (x+k)^2 => y^2 = x^2 +2kx+k^2 So: x^2 +x^2 +2kx +k^2 = 25 Transposing terms and collecting like terms: 2x^2 +2kx +(k^2 -25) = 0 Using the discriminant: 4k^2 -4*2*(k^2 -25) = 0 Which is the same as: 4k^2 -8k^2 +200 = 0 Collecting like terms and subtracting 200 from both sides: -4k^2 = -200 Divide both sides by -4: k^2 = 50 Square root both sides: k = + or - the square root of 50 Therefore it follows that the possible values of k are plus or minus the square root of 50
-4k + 10 - k + 2 = 2k + 4k + 18Combine all the 'k' terms on the left side:-5k + 10 + 2 = 2k + 4k + 18Combine all the 'k' terms on the right side:-5k + 10 + 2 = 6k + 18Combine the numerical terms on the left side:-5k + 12 = 6k + 18Add 5k to each side:12 = 11k + 18Subtract 18 from each side:-6 = 11kDivide each side by 11:k = -6/11
x =√k+√k+√k…… ectx² = k + xx² - x = kx² - x + (1/2)² = k + (1/2)² factorise x² - x + (1/2)²(x + 1/2)² = k + 1/4(x + 1/2)² = (4k + 1)/4x + 1/2 = ± √(4k + 1)/2x = 1/2 ± √(4k + 1)/2it obviously has to be positivex = 1/2 + √(4k + 1)/2x = (1 + √(4k + 1))/2
4k-7 = 7 4k = 14 k = 3.5 or k = 7/2
31 = 3-4k 31-3 = -4k 28 = -4k Divide both sides of the equation by -4 to find the value of k: k = -7
8-4k = 40 (4k-8) - 8 = 40-8 4k = 32 4k/4 = 32/4 k =8
4k-64 = -60
2
q=4k+4uImproved Answer:-If: Q = 4k+4uThen: k = (4u-Q)/-4
-4k-2=10 -4k=10+2 -4k=12 k=-3
wait is that algerbra? then what equaiton
There are infinitely many of them.Take any positive integer k and let 0
Remember in basic Algebra we learned that all variables can be substituted as 1's If needed. So lets do that: -k - 4k = -1 - 4(1) = -5 So now we can rewrite this removing the 1's we put in: -k - 4k = -5k
J = K+6 K + J = 4K Replace J in the second equation K + (K + 6) = 4K K + K + 6 = 4K 2K + 6 = 4K Subtract 2K from each side 6 = 2K divide both sides by 2 3 = K So, Keisha is 3 and therefore John is 9